2018
DOI: 10.1039/c7ra11134g
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation improves thermal stability and transmittance in FOLED substrates based on nanocellulose films

Abstract: Bleached softwood pulp was used to prepare nanofibrillated cellulose (NFC) by mechanical grinding and a high-pressure homogenization process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Therefore, the initial blocking of the hydroxyl end group blocks to some extent the second degradation process (Persenaire et al, 2001). Works with other polymers also showed that their acetylation lead to an increase of the thermal stability of the modified polymer (Hung et al, 2017;Yang et al, 2018b).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the initial blocking of the hydroxyl end group blocks to some extent the second degradation process (Persenaire et al, 2001). Works with other polymers also showed that their acetylation lead to an increase of the thermal stability of the modified polymer (Hung et al, 2017;Yang et al, 2018b).…”
Section: Resultsmentioning
confidence: 99%
“…Luminescent nanocomposites with a nanocellulose matrix are light-weight, flexible, thin materials with sufficient mechanical strength. These nanocomposites can be used in a number of practical applications, including: miniature biosensors and chemosensors [12][13][14][15][16][17][18][19][20], photodetectors [21,22], organic light-emitting diodes [23,24], organic solar cells [25], anti-counterfeiting [26] and different photonics devices [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…FOLED displays will have a profound impact on the application of wearable and portable devices, and will be widely used with the continuous development of personal intelligent terminals [ 10 , 11 , 12 , 13 ]. With the growing sophistication of organic light-emitting materials and device technologies, FOLEDs are regarded as promising technology for future displays [ 6 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the quality of the substrate determines the performance and life expectancy of the device. The FOLED substrate should be smooth and flat, with good dimensional stability, high flexibility, good thermal stability, high transparency, and good barrier properties [ 14 ]. Additionally, substrate materials impact the following processes: electrode deposition, barrier coating, patterning exposure, and thin-film transistor fabrication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation